Identitas warga asli Dieng dengan keunikan ruwatan rambut gimbal - Khasanah, Isrofiah Laela; Sari, Tri Yunita; Ningtyas, Dina Nurayu; Lestari, Dwi Indah (Academy of Social Science and Global Citizenship Journal, 2021)
This research is motivated by the uniqueness of the community with dreadlocks in the Dieng Plateau area in the Banjarnegara area, Central Java. Ruwatan dreadlocks is believed to be the incarnation of Kyai Kolodete (guard Dieng). The research was conducted using literature studies and sourced from articles, journals, books and thesis results from various existing media, the results of the research conducted showed that the existence of dreadlocks treatment is still being carried out today as evidenced by the holding of the Dieng Culture Festival. The existence of this tradition is influenced by the many privileges contained in the implementation of the ruwatan. Then, the position of tradition that is still firmly held by the surrounding community proves the people's love for the existing culture does not fade with the cultures that keep coming from outside. This is what we must apply in social life in Indonesia.